Time-resolved product observation for CO2 electroreduction using synchronised electrochemistry-mass spectrometry with soft ionisation (sEC-MS-SI). - Zhang,G; Kucernak,A (Angewandte Chemie International Edition, 2023)
The mechanistic understanding of electrochemical CO2 reduction reaction (CO2 RR) requires a rapid and accurate characterisation of product distribution to unravel the activity and selectivity, which is yet hampered by the lack of advanced correlative approaches. Here, we present the time-resolved identification of CO2 RR products by using the synchronised electrochemistry-mass spectrometry (sEC-MS). Transients in product formation can be readily captured in relation to electrochemical conditions. Moreover, a soft ionisation (SI) strategy is developed in MS for the direct observation of CO, immune to the interference of CO2 fragments. With the sEC-MS-SI, the kinetic information, such as Tafel slopes and onset potentials, for a myriad of CO2 RR products are revealed and we show the hysteresis seen for the evolution of some species may originate from the potential-driven changes in surface coverage of intermediates. This work provides a real-time picture of the dynamic formation of CO2 RR products.